Cultivation of Cyanobacteria on Sustainable Dried Luffa cylindrica - Jonas Kollmen; Judith Stiefelmaier; Ramtin Mofrad; Dorina Strieth (Phycology, 2023)
Cyanobacteria are promising organisms for the sustainable production of various biotechnological interesting products. Due to their energy production via photosynthesis, the cultivation of cyanobacteria expands the CO2 cycle. Most cyanobacteria form biofilms on surfaces in their natural environment by surrounding the cells with a self-produced matrix of extracellular polymeric substances (EPS) that hold the cells together. These special growth properties need special reactors for cultivation. By immobilizing cyanobacteria on carriers, systems currently established in industry could also be used for biofilm formers. Various artificial carriers for immobilized growth of cyanobacteria and microalgae have already been described in the literature. However, the use of waste materials or natural biodegradable carriers would be more sustainable and is, therefore, the focus of this study. Dried Luffa cylindrica, zeolite, and corn stalks were investigated for their use as carriers for cyanobacteria. L. cylindrica was shown to be an excellent natural carrier for (i) Anabaena cylindrica, (ii) Nostoc muscorum 1453-12a, and (iii) Nostoc muscorum 1453-12b. Higher or at least similar growth rates were achieved when cyanobacteria were cultivated with L. cylindrica compared to submerged cultivation. Additionally, the production of EPS and C-phycocyanin was increased at least 1.4 fold in all strains by culturing on L. cylindrica. The improved growth could be explained on the one hand by the high surface area of L. cylindrica and its properties, and, on the other hand, by the release of growth-promoting nutrients from L. cylindrica to the medium.